SMOKING AMONG ADOLESCENT MALES AT PULAU WEH, INDONESIA - Knut Ragnvald Skulberg; Samarullah Hamid; Arild Vaktskjold (Public Health of Indonesia)
Background: Use of tobacco may cause severe diseases like cardiovascular diseases and lung cancer. Smoking is a major threat to public health in many low- and middle-income countries.